PELATIHAN MANAJEMEN DAN LABELING PADA KELOMPOK TANI SUBAK BENGKEL, DESA BENGKEL, KECAMATAN KEDIRI KABUPATEN TABANAN - Sumaryani, N. Putri; Ni Wayan Sunita; Ni Nyoman Parmithi; I Nengah Suka Widana (Sewagati, 2023)
Workshop Village, Kediri District, Tabanan Regency is a village whose population is 80% farmers. Bengkel Village has the largest subak land in Kediri District. Workshop Village is a Tourism Village with very beautiful natural potential and agricultural and cultural activities that are still very well preserved. The workshop village which has a close distance to Tanah lot makes the workshop village a strategic village to introduce rural tourism as well as various Subak activities and Other unspoiled cultural attractions. Bengkel Village is one of the villages that produces black rice with good quality, because the black rice produced in Bengkel Village has advantages with a small sugar content. However, marketing still experiences obstacles in the marketing and labeling process so that it becomes more attractive to be developed in the market.